Digital Ulcers: Multidisciplinary Approach and Dermatological Management - Starace, Michela; Orioni, Gionathan; Alessandrini, Aurora; Bruni, Francesca; Baraldi, Carlotta; Misciali, Cosimo; Piraccini, Bianca Maria (Dermatology Practical & Conceptual, 2023)
Introduction: Digital ulcers represent a current public health issue, due to the relevant difficulties in their management and their tendency to become chronic, non-healing lesions. We present an observational study of 28 patients referred to our Wound Care Service, focused on multidisciplinary and dermatological management. Objectives: Our case series represents an opportunity to discuss the main comorbidities that affect these kinds of patients and to present an evidence-based protocol that has proved highly effective in our clinical practice. Methods: We collected the clinical data of 28 patients referred to our Wound Care Service at S.Orsola-Malpighi Hospital, where they were all clinically evaluated; subsequently a local treatment was set up with dressings and the application of topical medications, while for most of them a further multidisciplinary evaluation was required to control the underlying disease and to avoid relapses. Results: Digital ulcers were divided into 5 categories, based on the causative agent: peripheral artery disease, diabetes associated wounds, mixed wounds, pressure wounds and immune-mediated diseases associated with wounds. Each group received a specific management, based on the characteristics of the ulcer and the underlying comorbidities. Conclusions: The clinical evaluation of digital wounds requires a thorough knowledge of the possible causes behind the onset of these ulcerative forms. In case of suspicion, send the patient for a specialist evaluation, to carry out a proper management of the case. A multidisciplinary approach in the management of these wounds is necessary to achieve a precise diagnosis and a correct treatment.